Extraordinary Reflection from Photonic Crystal with Metamaterials - Shmat'ko, A. A.; Kazanko, A. V.; Mizernik, V. N.; Odarenko, E. N.; Yampol'skii, V. A.; Rokhmanova, T. N. (IEEE, 2016)
We predict an extraordinary perfect reflection of a plane wave from a finite-thickness photonic crystal made of dielectrics and metamaterials. The physical nature of this phenomenon is revealed. We show that this complete reflection is related to a resonance of surface plasmon-polariton wave along the crystal thickness.
Keywords: photonic crystals; extraordinary reflection; mеtаmаterials; plasmon-polariton waves